2023
DOI: 10.32362/2500-316x-2023-11-5-63-70
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear magnetoelectric effect in a ring composite heterostructure

V. I. Musatov,
F. A. Fedulov,
D. V. Savelev
et al.

Abstract: Objectives. The relevance of the study of magnetoelectric (ME) effect in ring ferromagnetic–piezoelectric heterostructures is due to the possibility of creating various ME devices having improved characteristics. A detailed investigation of the nonlinear ME effect in a ring composite heterostructure based on lead zirconate titanate (PZT) piezoceramics and Metglas® amorphous ferromagnetic (FM) alloy under circular magnetization is presented.Methods. The ME effect was measured by the low-frequency magnetic field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A circumferential ac field and a bias dc field of 0.4 Oe were generated using a toroidal coil wound on the structure. Finally, in a Metglas/PZT ring structure, the effective generation of voltage harmonics was observed when the structure was excited by a circumferential field at a resonance frequency of 54 kHz in the absence of a bias dc field [16]. These investigations demonstrate the promise of using circumferentially magnetized ring structures, in which there are no demagnetization effects, as non-contact current sensors.…”
Section: Introductionmentioning
confidence: 67%
“…A circumferential ac field and a bias dc field of 0.4 Oe were generated using a toroidal coil wound on the structure. Finally, in a Metglas/PZT ring structure, the effective generation of voltage harmonics was observed when the structure was excited by a circumferential field at a resonance frequency of 54 kHz in the absence of a bias dc field [16]. These investigations demonstrate the promise of using circumferentially magnetized ring structures, in which there are no demagnetization effects, as non-contact current sensors.…”
Section: Introductionmentioning
confidence: 67%
“…An increase in the ME effect in such structures, as compared with structures containing only nickel or permendur layers, has been demonstrated. It has also been shown that the largest ME effect in ring structures occurs when both the excitation ac magnetic field and the dc bias magnetic field are directed circumfirentially [20,25]. In this case, due to the absence of demagnetization, the maximum ME effect was observed at lower dc bias fields.…”
Section: Introductionmentioning
confidence: 93%
“…The method of increasing the ME effect described above was implemented in planar composite structures. However, in recent years, interest in studying the ME effect in ringtype heterostructures, consisting of FM and PE layers, has grown significantly [16][17][18][19][20]. Such structures can be used in ac current sensors [21] and electrically tuned inductors [22].…”
Section: Introductionmentioning
confidence: 99%